Identification of TRIM14 as a Type I IFN-Stimulated Gene Controlling Hepatitis B Virus Replication by Targeting HBx - Tan, Guangyun; Xu, Fengchao; Song, Hongxiao; Yuan, Ye; Xiao, Qingfei; Ma, Feng; Qin, F. Xiao-Feng; Cheng, Genhong (Frontiers in Immunology, 2018)
Hepatitis B virus (HBV) remains a major cause of hepatic disease that threatens human health worldwide. Type I IFN (IFN-I) therapy is an important therapeutic option for HBV patients. The major antiviral effect of IFN is mediated by upregulating the expression of downstream IFN-stimulated genes (ISGs). However, the mechanisms by which IFN induces ISG production and inhibits HBV replication are yet to be clarified. TRIM14 was recently reported as a key molecule in the IFN signaling pathway which regulates IFN production in response to viral infection. In this study, we sought to understand the mechanisms by which IFN restricts HBV replication. We confirmed that TRIM14 is an ISG in the hepatic cells, and that the pattern-recognition receptor (PRR) ligands polyI:C and polydAdT induce TRIM14 dependent on IFN-I production. In addition, IFN-I–activated STAT1, but not STAT3, directly bound to the TRIM14 promoter and mediated the induction of TRIM14. Interestingly, TRIM14 played an important role in IFN-I–mediated inhibition of HBV, and the TRIM14 SPRY domain interacted with the C-terminal of HBx, which might block the role of HBx in facilitating HBV replication by inhibiting the formation of Smc-HBx-DDB1 complex. Thus, our study clearly demonstrates that TRIM14 is a STAT1-dependent ISG, and the IFN-I–TRIM14–HBx axis shows an alternative way to understand the mechanism by which IFN-I inhibits virus replication.